Evaluating the feasibility of implementing a Telesleep pilot program using two-tiered external facilitation - Nicholas A. Rattray; Andrew Khaw; Mackenzie McGrath; Teresa M. Damush; Edward J. Miech; Adam Lenet; Stephanie Stahl; Jared Ferguson; Jennifer Myers; David Guenther; Barbara J. Homoya; Dawn M. Bravata (BMC, 2020)
Abstract Background Obstructive sleep apnea (OSA) can negatively impact patients' health status and outcomes. Positive airway pressure (PAP) reverses airway obstruction and may reduce the risk of adverse outcomes. Remote monitoring of PAP (as opposed to in-person visits) may improve access to sleep medicine services. This study aimed to evaluate the feasibility of implementing a clinical program that delivers treatment for OSA through PAP remote monitoring using external facilitation as an implementation strategy. Methods Participants included patients with OSA at a Veteran Affairs Medical Center (VAMC). PAP adherence and clinical disease severity on treatment (measured by the apnea hypopnea index [AHI]) were the preliminary effectiveness outcomes across two delivery models: usual care (in-person) and Telehealth nurse-delivered remote monitoring. We also assessed visit duration and travel distance. A prospective, mixed-methods evaluation examined the two-tiered external facilitation implementation strategy. Results The pilot project included N = 52 usual care patients and N = 38 Telehealth nurse-delivered remote monitoring patients. PAP adherence and disease severity were similar across the delivery modalities. However, remote monitoring visits were 50% shorter than in-person visits and saved a mean of 72 miles of travel (median = 45.6, SD = 59.0, mode = 17.8, range 5.4-220). A total of 62 interviews were conducted during implementation with a purposive sample of 12 clinical staff involved in program implementation. Weekly external facilitation delivered to both front-line staff and supervisory physicians was necessary to ensure patient enrollment and treatment. Synchronized, "two-tiered" facilitation at the executive and coordinator levels proved crucial to developing the clinical and administrative infrastructure to support a PAP remote monitoring program and to overcome implementation barriers. Conclusions Remote PAP monitoring had similar efficacy to in-person PAP services in this Veteran population. Although external facilitation is a widely-recognized implementation strategy in quality improvement projects, less is known about how multiple facilitators work together to help implement complex programs. Two-tiered facilitation offers a model well-suited to programs where innovations span disciplines, disrupt professional hierarchies (such as those between service chiefs, clinicians, and technicians) and bring together providers who do not know each other, yet must collaborate to improve access to care.